Pengaruh Lifestyle, Viral Marketing, dan Price terhadap Keputusan Pembelian Produk Kosmetik Hanasui pada Masyarakat Desa Kemuning Kecamatan Tarik Kabupaten Sidoarjo Jawa Timur - Hasan, Aisyah Yuliana; Maruta, IGN Anom; Andayani, Sri (Research Journal of Social Science and Economics, 2025)
This study aims to determine the significant effect of Lifestyle, Viral Marketing, and Price on the Purchase Decision of Hanasui Cosmetic Products in the Public Desa Kemuning Kecamatan Tarik Kabupaten Sidoarjo Jawa Timur. This research approach uses quantitative methods, the media used is using the media questionnaire as a research instrument. The sampling method uses a non-probability approach with the type of accidental sampling technique and the technical analysis uses multiple linear regression with hypothesis testing, namely the t test, R2 test, and F test. The number of respondents is 100 people who have consumed or purchased Hanasui cosmetic products, using the IBM SPSS 22 data analysis program. The results of this study indicate that the Lifestyle, Viral Marketing, and Price variables have a positive and significant effect on the Decision to Purchase Hanasui Cosmetic Products in the Public Desa Kemuning Kecamatan Tarik Kabupaten Sidoarjo Jawa Timur. The effect of Lifestyle, Viral Marketing, and Price on Purchasing Decisions is 69.8% of these variables, while the remaining 30.2% is influenced by other variables not used in this study.